Chemistry, Pharmacology and Medicinal Property of Frankincense (Boswellia Species): From the Selection of Traditional Applications to the Novel Phytotherapy for the Prevention and Treatment of Serious Diseases. (Global Journal of Medical Research, 2015)
Frankincense, the resinous extract from the trees of the genus Boswellia, has been used for centuries in ceremonial, cosmetic, cultural and as a traditional medicine to treat a variety of ailments especially inflammatory diseases including asthma, arthritis, cerebral edema, chronic pain syndrome, chronic bowel diseases, cancer and some other illnesses. Boswellic acids are the active compounds of frankincense and AKBA (3-O-acetyl-11-keto-β-boswellic acid) is the most important and effective acid among them. Some studies have shown that the use of frankincense can also improve the learning and enhance the memory in animals and human. It seems that frankincense might have a potential ability to be used as an alternative natural medicine not only for chronic and inflammatory diseases but also for the patients with brain and memory disorders.
Keywords: boswellia species; anti-inflammatory; chronic diseases; cancer; memory enhancement